A land of lakes and fishers: the cultural and historical geography of the Lake Pátzcuaro landscape in postrevolutionary México - Aguilera Lara, Jahzeel (2021)
This thesis investigates the cultural and historical geography of the Lake Pátzcuaro region in Postrevolutionary Mexico. It covers a period of significant changes in México, following the end of the armed phase of the Mexican Revolution (1910-1920). My research also grapples with the domestic and global political changes in the context of WWII and how they shaped ongoing processes in the Lake Pátzcuaro region. Throughout the thesis I examine the ideas, practices, and events that shaped this place and people’s ways of relating to it, including ideas of national identity, indigeneity, environmental conservation programmes, scientific research, and continental integration. The purpose is to understand how these forms of relating to Lake Pátzcuaro emerged and how they came to define its character. The thesis investigates the process of becoming indigenous in Lake Pátzcuaro and its role in the creation of a national culture and identity, within the processes of construction of the nation-state after the Mexican Revolution. I do so by looking at the development of the postrevolutionary cultural programme in the Lake Pátzcuaro region, which transformed the region into an icon of national authenticity. Even so, national integration efforts were only partially fulfilled, insofar as they resulted in the articulation of indigenous identities. I then look at the production of Lake Pátzcuaro nature cultures and how it took part in the consolidation of power in the region, producing natural-political hybrids. This process involved the transformation of land property regimes, the production of scientific knowledge about the lake, the establishment of environmental protection schemes, as well as scientific forms of natural resource management. So that the creation of Mexico and the Mexican was not limited to the realm of culture but also involved nature. The protection of Pátzcuaro’s colonial architecture also contributed to the consolidation of the dominant discourses of Mexican identity, which established the colonial period as the founding moment of the modern Mexican nation. This involved regulating people’s architectural conduct regarding modifications to the built landscape. The set of practices and discourses outlined above were both enabling and restrictive, producing particular ways of being in the landscape that expressed visions of revolutionary citizenship. Finally, this work also explores the role of Lake Pátzcuaro in the development of international policies on indigenous peoples and its relationship with the development of Pan-Americanism. Indigenous peoples went from being the exclusive focus of national governments to being the centre of attention of international agencies, producing new geographies of indigeneity.